Triphalangeal thumb–polysyndactyly syndrome and syndactyly type IV are caused by genomic duplications involving the long range, limb-specific SHH enhancer. Issue 9 (16th April 2008) - Sun, M; Ma, F; Zeng, X; Liu, Q; Zhao, X-L; Wu, F-X; Wu, G-P; Zhang, Z-F; Gu, B; Zhao, Y-F; Tian, S-H; Lin, B; et al.
Abstract : Background: The Sonic hedgehog (SHH) protein produced in the zone of polarising activity (ZPA) is a major determinant of the identity and numbers of digits in early limb development. Preaxial polydactyly types II (PPD2) and III (PPD3) have been mapped to a critical region at 7q36, and subsequently shown to be caused by point mutations in the ZPA regulatory sequence (ZRS), a long range cis-regulator for the SHH gene. Triphalangeal thumb–polysyndactyly syndrome (TPTPS) and syndactyly type IV (SD4) were also mapped to the 7q36 region but pathogenic mutations in ZRS have not yet been affirmed. Methods and results: We performed linkage and haplotype analysis in six Han Chinese families with TPTPS and/or SD4, and refined the disease locus to an interval of 646 kb containing ZRS. In all families, the affected individuals heterozygous at rs10254391 (a single nucleotide polymorphism within ZRS) revealed a remarkable allele imbalance on sequence chromatogram. Using real-time quantitative polymerase chain reaction (qPCR), we identified duplication of ZRS and found that this duplication segregated with the limb phenotypes in all families but was not detected in unaffected family members or in unrelated control individuals. The duplication was also confirmed by interphase fluorescence in situ hybridisation (FISH) in an affected individual. We designed 17 additional qPCR assays and defined the minimum duplications in all six families, ranging from 131kb to 398kb. Conclusion: Both TPTPS and SD4 are due to duplications involving ZRS, the limb specific SHH enhancer. Point mutations in the ZRS and duplications encompassing the ZRS cause distinctive limb phenotypes.